Análise dos documentos de patentes correlacionados a tecnologias verdes depositados por universidades públicas brasileiras - Silva, Maguel Souza da (2016)
This study identifies and analyzes the related patent documents to green technologies deposited by 21 Brazilian public universities at the Instituto Nacional da Propriedade Industrial (INPI) from 01/01/2005 to 31/12/2014, for a total of 294 documents. Data were collected in INPI patent basis during the month of September 2015 and entered into a Microsoft Excel spreadsheet in which we analyzed the variables related to patent documents (type, distribution of patent documents by Region and Federative Unit Brazilian, temporal evolution (date) of deposits and sections and subclasses of the International Patent Classification); to depositors (depositors universities, document distribution by university and field of green technologies, collaborative network, interaction between universities and companies and patent family); and variables related to the inventors (number of inventors by document type authored by technology class area of operation). The survey results revealed the predominance of documents of the type patent. The Southeast Region and the State of São Paulo stand out as larger depositors. It identified the increase in deposits in 2007 and 2011. It was observed that the classification of related patent applications for green technologies are concentrated in section C - Chemistry and Metallurgy. The Universidade Estadual de Campinas (UNICAMP) appears as the institution with the highest number of patent applications filed with the INPI. It was found that the largest number of documents was present in the waste management field, and the Universidade Federal de Minas Gerais (UFMG) the institution that made more deposits in this field. The Universidade de São Paulo (USP) has the largest number of employees and the Universidade Federal do Rio de Janeiro (UFRJ) has the largest number of deposits made in conjunction with companies. The withdrawal of deposits from the perspective of the inventors revealed that 88% of individuals listed as inventors related to a single patent application. Another aspect inherent to the inventors to be pointed out is the fact that 9.8% of these technologies in applications were developed individually; the others (90.2%) are the result of collaboration between two or more inventors. We sought to define the profile of green technologies developed by Brazilian public universities, with the indicator the patent document. Moreover, it is expected that this research will contribute to the expansion of studies on information technology in the context of Information Science.